2021
DOI: 10.1002/btpr.3193
|View full text |Cite
|
Sign up to set email alerts
|

Preventing pyruvate kinase muscle expression in Chinese hamster ovary cells curbs lactogenic behavior by altering glycolysis, gating pyruvate generation, and increasing pyruvate flux into the TCA cycle

Abstract: Deletion of the pyruvate kinase muscle (PKM) gene, which is involved in conversion of phosphoenolpyruvate to pyruvate, has been shown to curb lactogenic behavior in Chinese hamster ovary (CHO) cells. This study describes the generation of pyruvate kinase muscle isoforms 1 and 2 knockout (PKM‐KO) and pyruvate kinase muscle isoform‐1 knockout (PKM1‐KO) CHO host cells to understand metabolic shifts that reduce lactate secretion in these cells. Glucose and amino acids uptake levels in wild‐type (WT), PKM‐KO, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Lactate and ammonia are known to be major byproducts that limit cell growth and productivity and can affect glycosylation patterns at certain quantities in supernatant (Mulukutla et al, 2019). Alternative culture methodologies, media design, and metabolic engineering have all been employed in the past to lower lactate production (Tang et al, 2021; Wilkens et al, 2019).…”
Section: Crispr‐cas9‐mediated Gene Ko For Cell Line Engineeringmentioning
confidence: 99%
“…Lactate and ammonia are known to be major byproducts that limit cell growth and productivity and can affect glycosylation patterns at certain quantities in supernatant (Mulukutla et al, 2019). Alternative culture methodologies, media design, and metabolic engineering have all been employed in the past to lower lactate production (Tang et al, 2021; Wilkens et al, 2019).…”
Section: Crispr‐cas9‐mediated Gene Ko For Cell Line Engineeringmentioning
confidence: 99%
“…Metabolic engineering has also been employed to reduce lactate accumulation by either targeting enzymes in the glycolysis pathway or by improving the poor connectivity between the mitochondrial and cytosolic metabolic systems. These efforts include reducing the expression of enzymes such as pyruvate kinase muscle (PKM), lactate dehydrogenase A (LDHA), and pyruvate dehydrogenase kinases (PDHks) as well as overexpressing enzymes such as recombinant yeast pyruvate carboxylase (PYC2) enzyme and malate dehydrogenase‐2 (MDH‐2) (Chong et al, 2010; Gupta et al, 2017; Tang et al, 2021; Toussaint et al, 2016; Zhou et al, 2011). In these studies, reduction in lactate levels were observed along with a redirection of more pyruvate into the TCA cycle for oxidation in the mitochondria, higher specific productivities, and in some cases improved product quality (Chong et al, 2010; Gupta et al, 2017; Tang et al, 2021; Toussaint et al, 2016; Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%